Optimalisasi Produktivitas Pertanian melalui Inovasi Mesin Pencacah Pakan dan Pengolahan Limbah Ternak Berbasis Pemberdayaan Masyarakat - Ellisia Kumalasari; Fauzan Masykur; Novi Indah Riani (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Banjarejo Village, Pudak Subdistrict, Ponorogo Regency, has agricultural and livestock potential that has not been fully utilized, particularly in the management of animal feed and cattle waste. This community service activity aims to improve agricultural and livestock productivity through the application of appropriate technology, namely a feed chopper machine and the conversion of livestock waste into organic fertilizer. The methods applied included socialization, training, and hands-on practice with farmers and livestock breeders over six months, accompanied by monitoring and evaluation of the technology’s effectiveness. The machine is assembled by utilizing a number of important components, including Diesel Matrix 6.5 G200 with 6.5 Hp power, strip plate, eser concrete, angle plate, hinge, 19 mm and 30 mm threaded axle, filter, B8 pulley system with V-belt, eser plate, and rubber wheels as mobility support. The implementation of this machine is expected to be able to provide a real contribution in increasing agricultural and livestock productivity through the use of appropriate technology that is more efficient, environmentally friendly, and oriented towards sustainability. The results showed an increase in feed efficiency by up to 40%, an average rise of 35% in milk production, and approximately 30% improvement in the quality of organic crops due to the use of compost fertilizer. This activity also enhanced the community’s understanding of sustainable local resource management and opened opportunities for business diversification in the agricultural and livestock sectors.